Magnesium alloy surface corrosion conversion method
By converting corrosion products into dense magnesium-containing carbonate layer on the surface of the magnesium alloy, the problem of irreversible corrosion on the surface of the magnesium alloy is solved, significantly improving the corrosion resistance of the magnesium alloy and realizing its recycling.
Patent Information
- Application Number
- CN202510017273.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
Surface corrosion of magnesium alloys is an irreversible process. The prior art is difficult to effectively remove corrosion products and form a dense protective layer, resulting in insufficient corrosion resistance of magnesium alloys in corrosive media environments.
By placing the magnesium alloy in a solution containing a corrosive medium and adding carbonate to the solution, the corrosion products on the surface of the magnesium alloy are removed and a dense magnesium-containing carbonate layer is formed. The method includes adjusting the pH value of the solution to 10, using sodium carbonate or other carbonate forms, controlling the concentration and reaction time of the carbonate to ensure that the resulting magnesium-containing carbonate layer has excellent anticorrosion effect.
The corrosion product film on the surface of the magnesium alloy is converted into a dense protective layer in situ, which significantly improves the corrosion resistance of the magnesium alloy in a corrosive medium environment, reduces the corrosion current density, and enables the corroded magnesium alloy to be recycled.
Smart Images

Figure CN119800344A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal surface corrosion treatment, and in particular to a method for converting rust on the surface of a magnesium alloy. Background Art
[0002] Magnesium has a low electrode potential, active chemical properties, and is prone to corrosion. At the same time, the corrosion of magnesium alloys is an irreversible process. After corrosion occurs, the surface of the magnesium alloy is covered with a loose and non-dense MgO / Mg(OH)2 corrosion product film. The PB ratio (the ratio of the volume of metal ions in the surface oxide film to the matrix, it is generally believed that the film layer with a PB ratio between 1-2 has good compactness, and the film layer with a PB ratio less than 1 or greater than 2 is prone to rupture and poor compactness) of this corrosion product film is less than 1, which is not enough to protect the magnesium alloy matrix from the erosion of corrosive media, and the corrosion of the magnesium alloy will continue to expand.
[0003] There are many methods for corrosion protection of magnesium alloys, but none of them can completely prevent corrosion. Although optimizing alloy composition can improve corrosion resistance, it is difficult to achieve stainless magnesium in an ideal state; although coatings are easy to prepare, they are easily damaged during use; corrosion inhibitors are used in small amounts and have low costs, but the occurrence of corrosion cannot be completely suppressed.
[0004] At present, the rust removal methods for magnesium alloys are mainly physical methods such as shot blasting, and there is no in-situ conversion method for the corrosion product film of magnesium alloys, such as using the rust conversion method to replace the loose corrosion product film on the surface of magnesium alloys with a dense protective layer with a PB ratio between 1 and 2. Therefore, how to achieve the reversibility and densification of the corrosion product film on the surface of magnesium alloys is an urgent problem to be solved. Summary of the invention
[0005] Based on this, it is necessary to provide a method for converting rust on the surface of a magnesium alloy, which can remove corrosion products on the surface of the magnesium alloy and simultaneously form a dense coating with excellent anti-corrosion effect.
[0006] The present application provides a method for converting rust on the surface of a magnesium alloy, comprising the following steps:
[0007] placing the magnesium alloy in a solution containing a corrosive medium so that the surface of the magnesium alloy corrodes;
[0008] Carbonate is added to the solution containing the corrosive medium to remove corrosion products on the surface of the magnesium alloy and form a magnesium-containing carbonate layer.
[0009] In some embodiments, in the solution containing the corrosive medium, the concentration of the carbonate is 0.005 mol / L to 1 mol / L.
[0010] In some embodiments, the magnesium carbonate layer has a thickness of 500 nm to 3000 nm.
[0011] In some embodiments, the time for forming the magnesium carbonate layer is 1 hour to 96 hours.
[0012] In some embodiments, after adding carbonate to the solution containing the corrosive medium, the method further includes adjusting the pH value of the solution containing the corrosive medium to 10.
[0013] In some embodiments, the method of adjusting the pH value of the solution containing the corrosive medium to 10 is to add an inorganic acid to the solution containing the corrosive medium;
[0014] Optionally, the inorganic acid is nitric acid.
[0015] In some embodiments, placing the magnesium alloy in a solution containing a corrosive medium means soaking the magnesium alloy in the solution containing a corrosive medium for 1 hour to 3 hours.
[0016] In some embodiments, the solution containing the corrosive medium includes one or more of a salt solution containing chloride ions, a salt solution containing sulfate ions, and an inorganic acid solution;
[0017] Optionally, the concentration of the solution containing the corrosive medium is 0.2 mol / L to 0.6 mol / L.
[0018] In some embodiments, the magnesium alloy is one or more of an AZ series magnesium alloy, a ZK series magnesium alloy, and a WE series magnesium alloy.
[0019] In some embodiments, before placing the magnesium alloy in a solution containing a corrosive medium, the method further includes grinding and cleaning the magnesium alloy.
[0020] The magnesium alloy surface rust conversion method provided in the present application can remove the loose porous corrosion products on the magnesium alloy surface while covering it with a dense magnesium-containing carbonate layer. This method can convert the corrosion product film on the surface of the magnesium alloy into a dense protective layer in situ, so that the corroded magnesium alloy can be recycled, and at the same time greatly improve the corrosion resistance of the magnesium alloy in an environment containing corrosive media.
[0021] Furthermore, the preparation method provided in the present application has the advantages of low cost, simple operation, environmental friendliness and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 The electrochemical impedance performance test result diagram of the magnesium alloy after rust conversion obtained in Examples 1 to 12 and Comparative Examples 1 to 3;
[0024] Figure 2 The scanning electron microscope images of the corroded magnesium alloy and the magnesium alloy after rust conversion obtained in Examples 1 to 4 and Comparative Example 1;
[0025] Figure 3 X-ray diffraction patterns of the magnesium alloys after rust conversion obtained in Examples 1 to 4 and Comparative Example 1;
[0026] Figure 4 The cross-sectional morphology of the magnesium alloys after rust conversion obtained in Examples 1 to 4, 9 to 12 and Comparative Examples 1 and 3;
[0027] Figure 5 The transmission morphology images of the magnesium alloys after rust conversion obtained in Examples 2 and 10;
[0028] Figure 6 The polarization curve test results of the corroded magnesium alloy and the magnesium alloy after rust conversion obtained in Example 2 in 0.6 mol / L sodium chloride solution. DETAILED DESCRIPTION
[0029] In order to facilitate understanding of the present application, the present application is described more comprehensively below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0031] the term:
[0032] In this article, unless otherwise specified, "one or more" means any one of the listed items or any combination of the listed items. Similarly, "one or more" and other expressions that mean "one or more" are also understood in the same way unless otherwise specified.
[0033] Herein, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If multiple "optional" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" item is independent of each other. In this application, descriptions such as "optionally contain", "optionally include", etc. mean "contain or not contain". "Optional component X" means that component X exists or does not exist, or means that component X is contained or not contained.
[0034] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0035] Herein, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.
[0036] In this article, if there are multiple steps involved in the method flow, unless there is a clear different description in this article, there is no strict order restriction for the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.
[0037] The present application provides a method for converting and treating rust on the surface of a magnesium alloy, comprising step S200 and step S300.
[0038] The magnesium alloy surface rust conversion method provided in the present application can remove the loose porous corrosion products on the magnesium alloy surface while covering it with a dense magnesium-containing carbonate layer. This method can convert the corrosion product film on the surface of the magnesium alloy into a dense protective layer in situ, so that the corroded magnesium alloy can be recycled, and at the same time greatly improve the corrosion resistance of the magnesium alloy in an environment containing corrosive media.
[0039] Furthermore, the preparation method provided in the present application has the advantages of low cost, simple operation, environmental friendliness and high efficiency.
[0040] After the magnesium alloy surface rust conversion method provided by the present application is used to remove the corrosion products on the magnesium alloy surface and simultaneously form a dense magnesium-containing carbonate layer, the impedance of the corroded magnesium alloy can be reduced from 200Ω·cm 2 Increased to 2300Ω·cm 2 , increased by about 11 times; the corrosion current density increased from 2.93×10 -5 A / cm 2 Reduced to 6.18×10 -6 A / cm 2 , reduced to one-fifth of the original.
[0041] Step S200: placing the magnesium alloy in a solution containing a corrosive medium to cause corrosion on the surface of the magnesium alloy.
[0042] In some embodiments, the magnesium alloy is one or more of AZ series magnesium alloy, ZK series magnesium alloy and WE series magnesium alloy. The AZ series magnesium alloy refers to a magnesium alloy with aluminum and zinc as main elements; specifically, the AZ series magnesium alloy includes AZ31 magnesium alloy, AZ61 magnesium alloy, AZ91 magnesium alloy, etc.; the ZK series magnesium alloy refers to a magnesium alloy with zinc and zirconium as main elements; specifically, the ZK series magnesium alloy includes ZK30 magnesium alloy, ZK60 magnesium alloy, ZK61 magnesium alloy, etc.; the WE series magnesium alloy refers to a magnesium alloy with yttrium and rare earth elements as main elements; specifically, the WE series magnesium alloy includes WE43 magnesium alloy, WE54 magnesium alloy, WE94 magnesium alloy, etc.
[0043] In some embodiments, the solution containing the corrosive medium includes one or more of a salt solution containing chloride ions, a salt solution containing sulfate ions, and an inorganic acid solution.
[0044] Wherein, the chloride ion-containing salt solution includes one or more of sodium chloride solution and / or potassium chloride solution. Preferably, the chloride ion-containing salt solution is sodium chloride solution.
[0045] The salt solution containing sulfate ions includes one or more of a sodium sulfate solution and a potassium sulfate solution.
[0046] The inorganic acid solution includes one or more of hydrochloric acid, sulfuric acid and phosphoric acid.
[0047] In some embodiments, the concentration of the solution containing the corrosive medium is 0.2 mol / L to 0.6 mol / L, for example, 0.2 mol / L, 0.4 mol / L, or 0.6 mol / L.
[0048] In some embodiments, placing the magnesium alloy in a solution containing a corrosive medium means soaking the magnesium alloy in the solution containing a corrosive medium for 1 hour to 3 hours.
[0049] In some embodiments, the corrosion product film formed after the surface of the magnesium alloy is corroded is a magnesium hydroxide film.
[0050] In some embodiments, the corrosion product film has a thickness of 4 μm to 8 μm.
[0051] In some embodiments, before placing the magnesium alloy in a solution containing a corrosive medium, step S100 is further included: grinding and cleaning the magnesium alloy. The grinding can be performed by any known method in the art, and for example, sandpaper can be used for grinding; further, the sandpaper can be sandpaper of model 1500 or model 3000. Specifically, sandpaper of model 1500 and sandpaper of model 3000 can be used for grinding in sequence. Cleaning specifically refers to cleaning the magnesium alloy with water and ethanol in sequence.
[0052] Step S300: adding carbonate to the solution containing the corrosive medium to remove corrosion products on the surface of the magnesium alloy and form a magnesium-containing carbonate layer.
[0053] In some embodiments, the carbonate salt comprises one or more of sodium carbonate and sodium bicarbonate.
[0054] In some embodiments, the magnesium carbonate layer comprises magnesium carbonate trihydrate (MgCO3·3H2O) and a composite product of magnesium carbonate trihydrate and magnesium hydroxide (MgCO3·Mg(OH)2·3H2O).
[0055] In some embodiments, in the solution containing the corrosive medium, the concentration of the carbonate is 0.005 mol / L to 1 mol / L, for example, 0.01 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.5 mol / L.
[0056] By selecting carbonates of different concentrations, the anti-corrosion effect of the formed magnesium-containing carbonate layer can be further regulated, thereby increasing the impedance of the corroded magnesium alloy and reducing the corrosion current density.
[0057] Preferably, the concentration of the carbonate is 0.2 mol / L to 0.5 mol / L.
[0058] In some embodiments, the magnesium carbonate layer has a thickness of 500 nm to 3000 nm, for example, 500 nm, 700 nm, 900 nm, 1100 nm, 1300 nm, 1500 nm, 2000 nm, 2500 nm, or 3000 nm.
[0059] In some embodiments, after adding carbonate to the solution of the corrosive medium, the method further includes adjusting the pH value of the solution of the corrosive medium to 10. By adjusting the pH value to 10, the formed magnesium-containing carbonate layer can be made more dense and uniform.
[0060] In some embodiments, the method of adjusting the pH value of the solution of the corrosive medium to 10 is to add an inorganic acid to the solution containing the corrosive medium;
[0061] Optionally, the inorganic acid is nitric acid. Compared with sulfuric acid or hydrochloric acid, the use of nitric acid can prevent the formation of the magnesium-containing carbonate layer from being interfered by other ions.
[0062] In some embodiments, the time for forming the magnesium-containing carbonate layer is 1 hour to 96 hours, for example, 24 hours, 48 hours, 72 hours, 96 hours. Preferably, the time for forming the magnesium-containing carbonate layer is 24 hours to 96 hours.
[0063] In some embodiments, the method for converting the rust on the surface of a magnesium alloy comprises the following steps:
[0064] Step S100: grinding the magnesium alloy with sandpaper and then washing it with water and ethanol;
[0065] Step S200: immersing the magnesium alloy obtained in step S100 in a solution containing a corrosive medium for 1 hour to 3 hours to cause corrosion on the surface of the magnesium alloy;
[0066] Step S300: adding carbonate to the solution of the magnesium alloy obtained in step S200, and stirring for 1 min to 30 min;
[0067] Step S400: adding an inorganic acid to the solution of the magnesium alloy obtained in step S300 to adjust the pH value of the solution to 10, and soaking for 1 hour to 96 hours.
[0068] The present application is further described in detail below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are preferably referred to the guidance given in the present application, and can also be based on the experimental manuals or conventional conditions in the art, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0069] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.
[0070] Example 1
[0071] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0072] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0073] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy to form a magnesium hydroxide film with a thickness of 4 μm to 8 μm. The scanning electron microscope image of the magnesium alloy after corrosion is as follows: Figure 2 The polarization curve of the corroded magnesium alloy in 0.6 mol / L sodium chloride solution is shown in Figure 6 As shown, it has been corroded. Then add sodium carbonate and stir to dissolve, and ensure that the concentration of sodium carbonate in the solution is 0.2 mol / L (M). Then adjust the pH of the sodium chloride solution containing sodium carbonate to 10 with nitric acid, and continue to immerse the magnesium alloy for 96 hours to perform rust conversion, while removing the corrosion products on the surface and forming a magnesium-containing carbonate layer, so that the thickness of the surface layer of the sample (including magnesium hydroxide corrosion products and magnesium-containing carbonate layer) is reduced from about 250μm to 500nm~3000nm.
[0074] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1 (c) is shown, that is, 0.2M. The scanning electron microscope image (SEM image) of the magnesium alloy after corrosion conversion obtained in this embodiment is as follows Figure 2 The X-ray diffraction pattern (XRD pattern) of the magnesium alloy after rust conversion obtained in this embodiment is as shown in FIG. Figure 3 The cross-sectional morphology of the magnesium alloy after corrosion conversion obtained in this embodiment is shown in FIG4(h), that is, 0.2M-96h.
[0075] Example 2
[0076] The preparation method of Example 2 is substantially the same as that of Example 1, except that the concentration of sodium carbonate is 0.5 mol / L (M); the specific steps are as follows:
[0077] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0078] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0079] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy, forming a magnesium hydroxide film with a thickness of 4 μm to 8 μm. Then sodium carbonate is added and stirred to dissolve, and the concentration of sodium carbonate in the solution is ensured to be 0.5 mol / L. Subsequently, the pH of the sodium chloride solution containing sodium carbonate is adjusted to 10 with nitric acid, and the magnesium alloy is immersed for 96 hours to perform rust conversion, and a magnesium carbonate layer is formed while removing the corrosion products on the surface, so that the thickness of the surface layer of the sample (including magnesium hydroxide corrosion products and magnesium carbonate layer) is reduced from about 250 μm to about 500 nm.
[0080] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1 (c) is shown, that is, 0.5M. The scanning electron microscope image (SEM image) of the magnesium alloy after corrosion conversion obtained in this embodiment is as follows Figure 2 The X-ray diffraction pattern (XRD pattern) of the magnesium alloy after corrosion conversion obtained in this embodiment is as shown in FIG. Figure 3 The cross-sectional morphology of the magnesium alloy after corrosion conversion obtained in this embodiment is shown in 4(j), i.e. 0.5M-96h. The transmission morphology of the magnesium alloy after corrosion conversion obtained in this embodiment is shown in 5(d) to (h), i.e. 0.5M-96h. The polarization curve of the magnesium alloy after corrosion conversion obtained in this embodiment in 0.6mol / L sodium chloride solution is shown in Figure 6 As shown, that is, 0.5M-96h.
[0081] Example 3
[0082] The preparation method of Example 3 is substantially the same as that of Example 1, except that the concentration of sodium carbonate is 0.01 mol / L (M); the specific steps are as follows:
[0083] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0084] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0085] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy, forming a magnesium hydroxide film with a thickness of 4 μm to 8 μm. Then sodium carbonate is added and stirred to dissolve, and the concentration of sodium carbonate in the solution is ensured to be 0.01 mol / L. Subsequently, the pH of the sodium chloride solution containing sodium carbonate is adjusted to 10 with nitric acid, and the magnesium alloy is immersed for 96 hours to perform rust conversion, and a magnesium carbonate layer is formed while removing the corrosion products on the surface, so that the thickness of the surface layer of the sample (including magnesium hydroxide corrosion products and magnesium carbonate layer) is reduced from about 250 μm to about 70 μm.
[0086] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1 (c) is shown, that is, 0.01M. The scanning electron microscope image (SEM image) of the magnesium alloy after corrosion conversion obtained in this embodiment is as follows Figure 2 The X-ray diffraction pattern (XRD pattern) of the magnesium alloy after corrosion conversion obtained in this embodiment is as shown in FIG. Figure 3 As shown, that is, 0.01M. The cross-sectional morphology of the magnesium alloy after corrosion conversion obtained in this embodiment is shown in Figures 4 (d1) to (d2), that is, 0.01M-96h.
[0087] Example 4
[0088] The preparation method of Example 4 is substantially the same as that of Example 1, except that the concentration of sodium carbonate is 0.1 mol / L (M); the specific steps are as follows:
[0089] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0090] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0091] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy, forming a magnesium hydroxide film with a thickness of 4 μm to 8 μm. Then sodium carbonate is added and stirred to dissolve, and the concentration of sodium carbonate in the solution is ensured to be 0.1 mol / L. Subsequently, the pH of the sodium chloride solution containing sodium carbonate is adjusted to 10 with nitric acid, and the magnesium alloy is immersed for 96 hours to perform rust conversion, and a magnesium carbonate layer is formed while removing the corrosion products on the surface, so that the thickness of the surface layer of the sample (including magnesium hydroxide corrosion products and magnesium carbonate layer) is reduced from about 250 μm to 4 μm to 12 μm.
[0092] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1 (c) shows, that is, 0.1M. The scanning electron microscope image (SEM image) of the magnesium alloy after corrosion conversion obtained in this embodiment is as follows Figure 2 The X-ray diffraction pattern (XRD pattern) of the magnesium alloy after corrosion conversion obtained in this embodiment is as shown in FIG. Figure 3 The cross-sectional morphology of the magnesium alloy after corrosion conversion obtained in this embodiment is shown in FIG4(f), that is, 0.1M-96h.
[0093] Example 5
[0094] The preparation method of Example 5 is substantially the same as that of Example 1, except that after the pH value is adjusted with nitric acid, the immersion time of the magnesium alloy is 1 hour; the specific steps are as follows:
[0095] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0096] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0097] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy, forming a magnesium hydroxide film with a thickness of 4 μm to 8 μm. Then sodium carbonate is added and stirred to dissolve, and the concentration of sodium carbonate in the solution is ensured to be 0.2 mol / L. Subsequently, the pH of the sodium chloride solution containing sodium carbonate is adjusted to 10 with nitric acid, and the magnesium alloy is immersed for another hour to perform rust conversion, and a magnesium-containing carbonate layer is formed while removing the corrosion products on the surface.
[0098] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1 As shown in (a), that is, 0.2M.
[0099] Example 6
[0100] The preparation method of Example 6 is substantially the same as that of Example 2, except that after the pH value is adjusted with nitric acid, the immersion time of the magnesium alloy is 1 hour; the specific steps are as follows:
[0101] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0102] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0103] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy, forming a magnesium hydroxide film with a thickness of 4 μm to 8 μm. Then sodium carbonate is added and stirred to dissolve, and the concentration of sodium carbonate in the solution is ensured to be 0.5 mol / L. Subsequently, the pH of the sodium chloride solution containing sodium carbonate is adjusted to 10 with nitric acid, and the magnesium alloy is immersed for another hour to perform rust conversion, and a magnesium-containing carbonate layer is formed while removing the corrosion products on the surface.
[0104] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1 As shown in (a), that is, 0.5M.
[0105] Example 7
[0106] The preparation method of Example 7 is substantially the same as that of Example 3, except that after the pH value is adjusted with nitric acid, the immersion time of the magnesium alloy is 1 hour; the specific steps are as follows:
[0107] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0108] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0109] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy, forming a magnesium hydroxide film with a thickness of 4 μm to 8 μm. Then sodium carbonate is added and stirred to dissolve, and the concentration of sodium carbonate in the solution is ensured to be 0.01 mol / L. Subsequently, the pH of the sodium chloride solution containing sodium carbonate is adjusted to 10 with nitric acid, and the magnesium alloy is immersed for another hour to perform rust conversion, and a magnesium-containing carbonate layer is formed while removing the corrosion products on the surface.
[0110] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1As shown in (a), that is, 0.01M.
[0111] Example 8
[0112] The preparation method of Example 8 is substantially the same as that of Example 4, except that after the pH value is adjusted with nitric acid, the immersion time of the magnesium alloy is 1 hour; the specific steps are as follows:
[0113] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0114] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0115] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy, forming a magnesium hydroxide film with a thickness of 4 μm to 8 μm. Then sodium carbonate is added and stirred to dissolve, and the concentration of sodium carbonate in the solution is ensured to be 0.1 mol / L. Subsequently, the pH of the sodium chloride solution containing sodium carbonate is adjusted to 10 with nitric acid, and the magnesium alloy is immersed for another hour to perform rust conversion, and a magnesium-containing carbonate layer is formed while removing the corrosion products on the surface.
[0116] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1 As shown in (a), that is, 0.1M.
[0117] Example 9
[0118] The preparation method of Example 9 is substantially the same as that of Example 1, except that after the pH value is adjusted with nitric acid, the immersion time of the magnesium alloy is 24 hours; the specific steps are as follows:
[0119] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0120] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0121] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy, forming a magnesium hydroxide film with a thickness of 4 μm to 8 μm. Then sodium carbonate is added and stirred to dissolve, and the concentration of sodium carbonate in the solution is ensured to be 0.2 mol / L. Subsequently, the pH of the sodium chloride solution containing sodium carbonate is adjusted to 10 with nitric acid, and the magnesium alloy is immersed for 24 hours to perform rust conversion, and a magnesium carbonate layer is formed while removing the corrosion products on the surface, so that the thickness of the surface layer of the sample (including magnesium hydroxide corrosion products and magnesium carbonate layer) is reduced from about 53 μm to 0.5 μm to 16 μm.
[0122] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1 (b), i.e. 0.2M. The cross-sectional morphology of the magnesium alloy after corrosion conversion obtained in this example is shown in FIG4(g), i.e. 0.2M-24h.
[0123] Example 10
[0124] The preparation method of Example 10 is substantially the same as that of Example 2, except that after the pH value is adjusted with nitric acid, the immersion time of the magnesium alloy is 24 hours; the specific steps are as follows:
[0125] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0126] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0127] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy, forming a magnesium hydroxide film with a thickness of 4 μm to 8 μm. Then sodium carbonate is added and stirred to dissolve, and the concentration of sodium carbonate in the solution is ensured to be 0.5 mol / L. Subsequently, the pH of the sodium chloride solution containing sodium carbonate is adjusted to 10 with nitric acid, and the magnesium alloy is immersed for 24 hours to perform rust conversion, and a magnesium carbonate layer is formed while removing the corrosion products on the surface, so that the thickness of the surface layer of the sample (including magnesium hydroxide corrosion products and magnesium carbonate layer) is reduced from about 53 μm to 0.5 μm to 16 μm.
[0128] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1 (b), i.e. 0.5M. The cross-sectional morphology of the magnesium alloy after corrosion conversion obtained in this embodiment is shown in 4(i), i.e. 0.5M-24h. The transmission morphology of the magnesium alloy after corrosion conversion obtained in this embodiment is shown in 5(a) to (c), i.e. 0.5M-24h.
[0129] Embodiment 11
[0130] The preparation method of Example 11 is substantially the same as that of Example 3, except that after the pH value is adjusted with nitric acid, the immersion time of the magnesium alloy is 24 hours. The specific steps are as follows:
[0131] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0132] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0133] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy, forming a magnesium hydroxide film with a thickness of 4 μm to 8 μm. Then sodium carbonate is added and stirred to dissolve, and the concentration of sodium carbonate in the solution is ensured to be 0.01 mol / L. Subsequently, the pH of the sodium chloride solution containing sodium carbonate is adjusted to 10 with nitric acid, and the magnesium alloy is immersed for 24 hours to perform rust conversion, and a magnesium carbonate layer is formed while removing the corrosion products on the surface, so that the thickness of the surface layer of the sample (including magnesium hydroxide corrosion products and magnesium carbonate layer) is reduced from about 53 μm to about 7 μm.
[0134] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1 (b), i.e. 0.01M. The cross-sectional morphology of the magnesium alloy after corrosion conversion obtained in this example is shown in 4 (c1) to (c2), i.e. 0.01M-24h.
[0135] Example 12
[0136] The preparation method of Example 12 is substantially the same as that of Example 4, except that after the pH value is adjusted with nitric acid, the immersion time of the magnesium alloy is 24 hours; the specific steps are as follows:
[0137] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0138] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0139] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy, forming a magnesium hydroxide film with a thickness of 4 μm to 8 μm. Then sodium carbonate is added and stirred to dissolve, and the concentration of sodium carbonate in the solution is ensured to be 0.1 mol / L. Subsequently, the pH of the sodium chloride solution containing sodium carbonate is adjusted to 10 with nitric acid, and the magnesium alloy is immersed for 24 hours to perform rust conversion, and a magnesium carbonate layer is formed while removing the corrosion products on the surface, so that the thickness of the surface layer of the sample (including magnesium hydroxide corrosion products and magnesium carbonate layer) is reduced from about 53 μm to 4 μm to 12 μm.
[0140] The electrochemical impedance test results of the magnesium alloy obtained in this example are as follows: Figure 1 (b), i.e. 0.1M. The cross-sectional morphology of the magnesium alloy after corrosion conversion obtained in this example is shown in FIG4(e), i.e. 0.01M-24h.
[0141] Comparative Example 1
[0142] The preparation method of Comparative Example 1 is substantially the same as that of Example 1, except that no sodium carbonate solution is added, that is, the concentration of the sodium carbonate solution is 0 mol / L (M). The specific steps are as follows:
[0143] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0144] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0145] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy to form a magnesium hydroxide film with a thickness of 4 μm to 8 μm. The pH of the sodium chloride solution is then adjusted to 10 with nitric acid, and the magnesium alloy is immersed for 96 hours to form a surface layer with a thickness of about 250 μm (containing only magnesium hydroxide corrosion products).
[0146] The electrochemical impedance test results of the magnesium alloy obtained in this comparative example are as follows: Figure 1 (c) is shown, that is, 0M. The scanning electron microscope image (SEM image) of the magnesium alloy obtained in this comparative example is shown Figure 2 The cross-sectional morphology of the magnesium alloy after rust conversion obtained in this comparative example is shown in Figures 4(b1) to (b2), that is, 0M-96h.
[0147] Comparative Example 2
[0148] The preparation method of comparative example 2 is basically the same as that of comparative example 1, except that after the pH value is adjusted with nitric acid, the immersion time of the magnesium alloy is 1 hour. The specific steps are as follows:
[0149] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0150] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0151] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy to form a magnesium hydroxide film with a thickness of 4 μm to 8 μm. The pH of the sodium chloride solution is then adjusted to 10 with nitric acid, and the magnesium alloy is immersed for another hour.
[0152] The electrochemical impedance test results of the magnesium alloy obtained in this comparative example are as follows: Figure 1 As shown in (a), that is, 0M.
[0153] Comparative Example 3
[0154] The preparation method of comparative example 3 is basically the same as that of comparative example 1, except that after the pH value is adjusted with nitric acid, the immersion time of the magnesium alloy is 24 hours. The specific steps are as follows:
[0155] An AZ61 magnesium alloy extruded sheet with a size of 10 mm × 10 mm × 3 mm was used as the substrate.
[0156] 1) The surface of the magnesium alloy was polished smooth using sandpaper of type 1500 and 3000, and then the magnesium alloy was cleaned with deionized water and ethanol in turn until the surface was clean.
[0157] 2) The magnesium alloy obtained in step 1) is immersed in a sodium chloride solution with a concentration of 0.6 mol / L for 2 hours to cause corrosion on the surface of the magnesium alloy to form a magnesium hydroxide film with a thickness of 4 μm to 8 μm. The pH of the sodium chloride solution is then adjusted to 10 with nitric acid, and the magnesium alloy is immersed for another 24 hours to form a surface layer with a thickness of about 53 μm (containing only magnesium hydroxide corrosion products).
[0158] The electrochemical impedance test results of the magnesium alloy obtained in this comparative example are as follows: Figure 1 (b), i.e. 0M. The cross-sectional morphology of the magnesium alloy after corrosion conversion obtained in this comparative example is shown in 4 (a1) to (a2), i.e. 0M-24h.
[0159] It can be seen from the electrochemical impedance test results of the embodiments and the comparative examples that the present application can significantly improve the corrosion resistance of the magnesium alloy, enhance its impedance and reduce the corrosion current density by using different concentrations of sodium carbonate to convert the rust on the corroded magnesium alloy surface. By comparing the test results of Examples 1 and 2 with those of Examples 3 and 4, it can be seen that when the concentration of sodium carbonate is lower than 0.2 mol / L, the rust conversion effect is poor and the corrosion resistance enhancement effect of the sample is limited. Furthermore, it can be seen from the test results of Examples 1 to 4 and Examples 5 to 12 that when the concentration of sodium carbonate is 0.5 mol / L and the rust conversion time increases from short-term (1h-24h) to long-term (96h), the corrosion resistance of the corroded magnesium alloy is enhanced, and the impedance increases from 270Ω·cm 2 Increased to 2300Ω·cm 2 , increased by about 9 times. Figure 2 From the SEM images, it can be seen that the surface of the corroded magnesium alloy is covered with spherical loose corrosion products. After the rust conversion time reaches 96h, the spherical loose corrosion products on the surface of the magnesium alloy with a sodium carbonate concentration lower than 0.2mol / L are not completely removed, and the magnesium-containing carbonate layer generated at the same time is not smooth and dense; the spherical loose corrosion products on the surface of the magnesium alloy with a sodium carbonate concentration higher than 0.2mol / L are completely removed, and the magnesium-containing carbonate layer generated at the same time is smooth and dense. Figure 3 From the XRD graph, it can be seen that when the sodium carbonate concentration is 0.5 mol / L, no Mg(OH)2 peak can be detected on the surface of the magnesium alloy after 96 hours of corrosion conversion, indicating that the corrosion products on the surface of the corroded magnesium alloy are completely removed. At the same time, peaks corresponding to MgCO3·3H2O and MgCO3·Mg(OH)2·3H2O are detected, indicating that a magnesium-containing carbonate layer is generated on the sample surface while the corrosion products are removed. Figure 4 It can be seen from the cross-sectional morphology diagrams of the embodiments and the comparative examples that the surface of the samples that have not undergone rust conversion has been severely corroded, and the thickness of the corrosion product layer is greater than 50μm; when the concentration of sodium carbonate is lower than 0.2mol / L, the rust conversion effect is poor, and the loose and uneven corrosion products on the surface of the magnesium alloy are not removed. At the same time, the magnesium-containing carbonate layer generated on the surface is not smooth and dense enough, and is destroyed as the immersion time increases. The thickness of the surface layer is greater than 3μm; when the concentration of sodium carbonate is higher than 0.2mol / L, the rust conversion effect is good, and at the same time, the magnesium-containing carbonate layer generated on the surface becomes smoother and denser as the immersion time increases. When the immersion time increases to 96h, the thickness of the magnesium-containing carbonate layer is about 500nm. Figure 5 The transmission morphology of the magnesium alloy after rust conversion obtained in Examples 2 and 10 shows that when the sodium carbonate concentration is 0.5 mol / L, as the immersion time increases from 24 h to 96 h, the corrosion products on the surface of the magnesium alloy are completely removed, and the newly generated magnesium-containing carbonate layer is smoother and denser. Figure 6The polarization curve shows that when the concentration of sodium carbonate is 0.5 mol / L, the corrosion conversion effect is good. After 96 hours of corrosion conversion, the corrosion resistance of the corroded magnesium alloy is enhanced, and the corrosion current density increases from 2.93×10 -5 A / cm 2 Reduced to 6.18×10 -6 A / cm 2 , reduced to one fifth of the original.
[0160] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0161] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description may be used to interpret the scope of the claims.
Claims
1. A method for converting surface corrosion of a magnesium alloy, characterized in that: The following steps are involved: placing the magnesium alloy in a solution containing a corrosive medium so that the surface of the magnesium alloy corrodes; Carbonate is added to the solution containing the corrosive medium to remove corrosion products on the surface of the magnesium alloy and form a magnesium-containing carbonate layer.
2. The method according to claim 1, characterized in that In the solution containing the corrosive medium, the concentration of the carbonate is 0.005 mol / L to 1 mol / L.
3. The method according to claim 1, characterized in that The thickness of the magnesium carbonate layer is 500nm to 3000nm.
4. The method according to claim 1, characterized in that The time for forming the magnesium-containing carbonate layer is 1 hour to 96 hours.
5. The method according to claim 1, characterized in that After adding carbonate to the solution containing the corrosive medium, the method further includes adjusting the pH value of the solution containing the corrosive medium to 10.
6. The method according to claim 5, characterized in that The method of adjusting the pH value of the solution containing the corrosive medium to 10 is to add an inorganic acid to the solution containing the corrosive medium; Optionally, the inorganic acid is nitric acid.
7. The method according to claim 1, characterized in that Placing the magnesium alloy in a solution containing a corrosive medium refers to immersing the magnesium alloy in the solution containing a corrosive medium for 1 hour to 3 hours.
8. The method according to any one of claims 1 to 7, characterized in that: The solution containing the corrosive medium includes one or more of a salt solution containing chloride ions, a salt solution containing sulfate ions, and an inorganic acid solution; Optionally, the concentration of the solution containing the corrosive medium is 0.2 mol / L to 0.6 mol / L.
9. The method according to any one of claims 1 to 7, characterized in that: The magnesium alloy is one or more of AZ series magnesium alloy, ZK series magnesium alloy and WE series magnesium alloy.
10. The method according to any one of claims 1 to 7, characterized in that: Before placing the magnesium alloy in the solution containing the corrosive medium, the method further includes the steps of grinding and cleaning the magnesium alloy.